Technical inefficiency and papaya farm size in West Africa: a stochastic frontier approach on Benin and Ghana data - Adeoti, R.; Coulibaly, O.; Agossou, D.; Goergen, Georg E.; Tamo, Manuele (2016)
Papaya is an emergent food and cash crop in Western Africa. It is used as an export crop in Ghana and for urban consumption in Benin. Papaya fruits are severely attacked by Papaya mealybug causing significant losses in quantity and quality. To control the papaya mealybug a classical biological control initiative has been developed and is environmental friendly. This study is targeting the production system efficiency and assesses key factors which influence the papaya production. It is conducted using cross-sectional data collected from papaya production systems in the sub-humid zones of West Africa. Results reveal that efficiency in producing papaya are still low in both countries. In Benin factors like land ownership remains important in the production performance, mainly in Ghana. Extension services and secured land tenure are incentives for producers to adopt better production practices to increase efficiency.